The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/aelm.202100042
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ferroelectric Properties in Hf0.5Zr0.5O2 Films Using a HfO0.61N0.72 Interfacial Layer

Abstract: Fluorite structured ferroelectrics, such as (Hf, Zr)O2, attract much interest due to their scalability and compatibility with complementary metal‐oxide semiconductors, which make them superior to the conventional ferroelectrics. However, their reliability issues, including their limited endurance, are yet to be resolved. Such issues have been reported to be strongly correlated to the formation and drift of oxygen vacancies concentrated in the interfacial region adjacent to TiN electrodes. In this study, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The recognizable polycrystalline of HfZrO layer is a characteristic of HfO 2 -based ferroelectric materials. 15,16) To further analyze the phase structure of the HfZrO layer, a Nano Beam Diffraction (NBD) is carried out. From the diffraction pattern, we calculate the interplanar distance which is about 2.92 Å by the Gatan Digital Micrograph and the result is in accord with (111) orthorhombic phase of HfO 2 -based ferroelectric materials.…”
Section: Resultsmentioning
confidence: 99%
“…The recognizable polycrystalline of HfZrO layer is a characteristic of HfO 2 -based ferroelectric materials. 15,16) To further analyze the phase structure of the HfZrO layer, a Nano Beam Diffraction (NBD) is carried out. From the diffraction pattern, we calculate the interplanar distance which is about 2.92 Å by the Gatan Digital Micrograph and the result is in accord with (111) orthorhombic phase of HfO 2 -based ferroelectric materials.…”
Section: Resultsmentioning
confidence: 99%
“…These layers adversely interfere with FE performance, resulting in polarization degradation and reliability issues. 7–10…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that a thin (1–2 nm) HfO x N y ( x = ∼0.61, y = ∼0.72) interfacial layer, grown by reactive sputtering, could efficiently suppress such adverse impacts by TiN oxidation. 9 The thin interfacial layers were in situ or ex situ oxidized during their growth and subsequent atomic layer deposition (ALD) of the Hf 0.5 Zr 0.5 O 2 (HZO) FE film. This oxidized interfacial layer protected the TiN film from oxidation-induced degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, with the discovery of ferroelectricity in fluorite structure in 2011, modern researchers put their attention to using these materials for advanced applications because of their low dielectric constant, simple structure, low leakage current, and small unit cell volume compared to perovskite and pyrochlore materials. 6,7 Ongoing development in smart electronic devices makes fluorite structure more imperative than others to be utilized for micromechanical and fast-switching applications. 8…”
Section: Introductionmentioning
confidence: 99%